Enhancing Massage Course Training in Sports Education through Validated and Practical Audio-Visual Learning Media - Selvani, Arif Selfa; Marheni, Eddy; Bakhtiar, Syahrial; Welis, Wilda; Purnomo, Eko; Ockta, Yovhandra (Universitas Pendidikan Ganesha, 2024)
This study addresses issues in teaching massage techniques within sports education programs, particularly concerning students' inadequate understanding and skill development. To enhance learning outcomes, this research and development (R&D) study employed the ADDIE model, focusing on the creation and validation of video-based learning media specifically designed for massage courses. The research subjects included material and media experts as well as sports education students from Padang State University. Validation results indicated that the video content met high academic and design standards, achieving scores of 88.33% from material experts and 94.54% from media experts. Practicality tests with students yielded positive feedback, with scores of 85.9% for the small group and 85.2% for the large group, demonstrating the media's effectiveness and user-friendliness. These findings suggest that video-based learning media can significantly improve understanding and engagement in complex subjects. This approach offers flexibility and supports diverse learning styles, potentially enhancing educational outcomes and fostering a more interactive learning environment.